Youth and change - (:unkn) unknown (Statistics Finland, 1992)
This book is an abridged, revised and updated edition of the original Finnish report (Nuoret ja muutos, ed. Jaana Lähteenmaa and Lasse Siurala) published in 1991 jointly by the Central Statistical Office (Statistics Finland), the Ministry of Education and the Youth Research Society.
Keywords: tilastot; nuoret; nuorisokulttuuri; koulutus; toimeentulo; vapaa-aika; aikuistuminen; hyvinvointi; Tutkimuksia, Working Papers